Celebrating IWMI at 40: learning from our history, turning to the future - Lenton, Roberto (International Water Management Institute, 2024)
This account, issued on IWMI’s 40th anniversary, describes the evolution and growth of IWMI from the idea stage to the present day. It has been prepared as a celebration not only of IWMI’s history and the vision of its founders but also of its contemporary character and culture. As such, it aims to introduce a wide range of IWMI stakeholders — current and future, IWMI leadership and staff, Board members, partners, and funders — to the “what, why, past, and future” of IWMI. A companion publication titled Inception: The creation of an international water management institute, 1969–1984 provides a full account of the creation of the institute, from 1969 to 1984, which is briefly summarized in the first section of this report.